"I'm Not Telling": The Effects of Racial Disparities Communications on Task Persistence Among Blacks. Issue 2 (1st February 2016) - Jones, Paul R.; Taylor, Dexter M.; Van Allen, Katherine L.; Dampeer-Moore, Jodi; Perrin, Andrew; Mullings, Raymond A.; Chapman, Tarik O.
Abstract : Research suggests that communications about racial health disparities may adversely affect Blacks. In this study, we varied the message content (Black–White cardiovascular-related disparities + neutral health topics vs. neutral health topics only) embedded in public service announcements given to Black and White participants ( N = 86) and had them complete a purported health self-assessment. We used the number of items completed as a measure of task persistence. Our results showed that participants in the disparities condition completed fewer items on average than participants in the neutral condition ( p < .01). Planned contrasts revealed that this effect was driven by the responses of Blacks who completed fewer items in the disparities condition ( p < .01), though Whites evinced a comparable condition-based trend ( p = .12). We found no Black–White differences in the number of items completed in either of our experimental conditions ( p s ≥ .53). Although preliminary, our findings suggest that Blacks and Whites exposed to comparative racial disparities messaging about cardiovascular diseases could experience reduced task persistence. Research implications and study limitations are also discussed.